Effectiveness of Article 53 On Marrying Pregnant Women In Compilation Of Islamic Law - Srirahma Srirahma; Sri Nanang Meiske Kamba (Universitas Negeri Gorontalo, 2022)
The purpose of this writing is to find out how effective Article 53 of the Compilation of Islamic Law is for pregnant women married to men who do not impregnate them in the case study of Tojo Una-Una Regency. The method used in this writing is by way of observation, interviews, and documentation. This type of writing is sociological juridical writing. Approach to an empirical sociological juridical analysis by going directly to the object or field. The type of data used is primary legal material and secondary legal material. The results of the writing show that article 53 of the Compilation of Islamic Law against pregnant women marrying men who do not impregnate them is not yet effective. The causal factors include internal factors and factors external. The legal consequences that arise are that it has an impact on the child to be born because it can question how the position, rights, maintenance, and when the birth is a girl, what about the guardian, as well as inheritance problems